HUBUNGAN ASUPAN ZAT GIZI MAKRO DENGAN STATUS GIZI MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS BAITURRAHMAH PADA ERA PANDEMI - Ivan M; Syolendra M. Hidayat; Jelmila Sri Nani (Yayasan Nusantara Hasana Berdikari, 2023)
Background: One of the efforts to prevent the spread of COVID-19 is to implement a healthy lifestyle. A healthy lifestyle is a way to increase the body's immunity by consuming lots of vegetables and fruits. Increasing body immunity can also be done by increasing rest time, maintaining nutrition, taking vitamins, maintaining mineral intake, doing sports and maintaining emotions. Objective: To determine the relationship between macronutrient intake and nutritional status of medical students at Baiturrahmah University during the pandemic era. Method: The scope of this research is nutrition science. The research was conducted in January 2021 - May 2022. The type of research is comparative numerical analysis and unpaired categorical analysis. The affordable population in this study were students majoring in Medicine, Faculty of Medicine, Baiturrahmah University during the pandemic era as many as 56 samples with purposive sampling technique. Univariate data analysis is presented in the form of mean and frequency distribution and bivariate analysis using One Way Anova test, data processing is using computerized program SPSS version IBM 25.0. Results: The average carbohydrate intake with normal nutritional status was (72.5% ± 22.11%). The highest average protein intake with normal nutritional status was (123.66% ± 45.27%), and the highest average fat intake with normal nutritional status was (82.50% ± 37.34%). Based on the results of statistical tests using the One Way Anova test, the results showed that there was no relationship between carbohydrate, protein, and fat intake on the nutritional status of students with p values respectively (p = 0.202), (p = 0.378), and (p = 0.534) or p value > 0.05. Conclusion: The most nutritional status was normal, the most carbohydrate intake was normal, the most fat intake was normal, the most protein intake was more, there was no relationship between carbohydrate intake and the nutritional status of students of the Faculty of Medicine, Baiturrahmah University in the pandemic era, there was no relationship between fat intake and nutritional status. nutrition of Baiturrahmah University Medical Faculty students in the pandemic era, and there is no relationship between protein intake and the nutritional status of Baiturrahmah University Medical Faculty students in the pandemic era.